The Pauline effect the use of the Pauline epistles by early Christian writers - Strawbridge, Jennifer R. 1978-; Walter de Gruyter GmbH & Co. KG (Berlin/Boston De Gruyter, Inc., 2015)
print_cont_9783110437706_Strawbridge_I-IV -- print_cont_9783110437706_Strawbridge.
Description based on publisher supplied metadata and other sources
Keywords: Paulus -- Apostel, Heiliger; Christian literature, Early ; History and criticism; Electronic books; Hochschulschrift